Establishment of the Reference Intervals of Lymphocyte Function in Healthy Adults Based on IFN-γ Secretion Assay upon Phorbol-12-Myristate-13-Acetate/Ionomycin Stimulation - Hou, Hongyan; Zhou, Yu; Yu, Jing; Mao, Lie; Bosco, Munyemana Jean; Wang, Juan; Lu, Yanfang; Mao, Liyan; Wu, Xiaohui; Wang, Feng; Sun, Ziyong (Frontiers in Immunology, 2018)
The function of lymphocytes is the key to reflect the immune status of hosts. Evaluation of lymphocyte function is a useful tool to monitor the effect of immunosuppressive treatment and predict the prognosis of immune-mediated diseases (eg, cancer, autoimmune diseases, and infectious diseases). As the lymphocytes have a variety of activities such as activation, cytotoxicity, and cytokine secretion, it is a challenge to evaluate the function of lymphocytes in clinical practice and the reference intervals (RIs) of lymphocyte function are rarely reported. The present study showed that the secretion of IFN-γ was well correlated with the activation, chemotaxis and cytotoxicity of CD4+, CD8+ T cells and NK cells, which suggests that IFN-γ production can be used as a symbol of lymphocyte function. We therefore created a simple method to detect the function of CD4+, CD8+ T cells and NK cells simultaneously according to IFN-γ secretion by using whole blood instead of peripheral blood mononuclear cells. We further established the RIs of lymphocyte function (CD4+ T cells: 15.31%-34.98%; CD8+ T cells: 26.11%-66.59%; NK cells: 39.43%-70.79%) in healthy adults. This method showed good reproducibility for the evaluation of lymphocyte function. The established RIs were suitable for use in other centers based on the validation data. We also validated the RIs in individuals with different immune status, and the results showed that kidney transplant recipients and infants (0-1 year) had a decreased lymphocyte function, whereas T cells in systemic lupus erythematosus patients exhibited an opposite trend. Overall, we have successfully established the RIs of lymphocyte function in healthy adults in a simple way, which might be of important clinical value in the diagnosis, monitoring, and prognosis of immune-related diseases.